Pemberian Reward Terhadap Karyawan Terbaik Dengan Mneggunakan Metode Simple Additive Weighting (SAW) - Ferly Ardhy; Dwi Marisa Efendi (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2019)
Multi attribute decission making (MADM) model, one of them is to use the simple additive weighting (SAW) method. This research is useful for giving rewards to employees, This research needs some criteria, they are  Age values, education, psychological tests, interviews, work experience, and health the result of this calculation i with the highest value on alternative A5 with a value of 85 and A6 with a value of 72.5 .